Re-imagining the nation : african nationalism, socio-political commitment and self-representation in sub-Saharan women’s novels - (:unkn) unknown (My University, 2011)
Nationalism in sub-Saharan Africa « imagines » a homogenous national identity embedded in the mythology of African uniqueness, which represents the woman symbol of cultural roots (the “Mother Africa “trope). This study analyses how the sub-Saharan female novelist (the woman as a mute, extra-historical and apolitical object of culture) appropriates African nationalism (re-imagines the nation) to define a new identity for African womanhood. The study tests the hypothesis that a marg...
Keywords: African Research